Cloning and Characterization of the Flavobacterium johnsoniae Gliding Motility Genes gldD and gldE - Hunnicutt, David W. (American Society for Microbiology, 2001)
Cells of Flavobacterium johnsoniae move over surfaces by a process known as gliding motility. The mechanism of this form of motility is not known. Cells of F. johnsoniae propel latex spheres along their surfaces, which is thought to be a manifestation of the motility machinery. Three of the genes that are required for F. johnsoniae gliding motility, gldA, gldB, and ftsX, have recently been described. Tn4351 mutagenesis was used to identify another gene, gldD, that is needed for gliding. Tn4351-induced gldD mutants formed nonspreading colonies, and cells failed to glide. They also lacked the ability to propel latex spheres and were resistant to bacteriophages that infect wild-type cells. Introduction of wild-type gldD into the mutants restored motility, ability to propel latex spheres, and sensitivity to bacteriophage infection. gldD codes for a cytoplasmic membrane protein that does not exhibit strong sequence similarity to proteins of known function. gldE, which lies immediately upstream of gldD, encodes another cytoplasmic membrane protein that may be involved in gliding motility. Overexpression of gldE partially suppressed the motility defects of a gldB point mutant, suggesting that GldB and GldE may interact. GldE exhibits sequence similarity to Borrelia burgdorferi TlyC and Salmonella enterica serovar Typhimurium CorC.